2020
DOI: 10.1371/journal.pone.0227854
|View full text |Cite
|
Sign up to set email alerts
|

Common mental illness among epilepsy patients in Bahir Dar city, Ethiopia: A cross-sectional study

Abstract: Background Common mental illness has a substantial impact on seizure control and negatively affects the overall quality of life among individuals with epilepsy. However, there is a dearth of studies that examined the associated factors of common mental illness among epilepsy patients in Ethiopia, particularly in the study area. This study aimed to assess the magnitude and factors associated with common mental disorders in epilepsy patients who attended government health institutions in Bahir Dar city, Ethiopia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…In most Ethiopian society especially in rural areas, women are expected to stay at home to care for their children and other home activities. In addition, women had a limitation of activities outside their homes, fewer opportunities for them in education and employment, and greater risk of domestic violence [14]. The other reason might be; women faced different hormonal changes at some stages of their life such as during menstruation cycle, pregnancy, and menopause which may predispose them to emotional changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most Ethiopian society especially in rural areas, women are expected to stay at home to care for their children and other home activities. In addition, women had a limitation of activities outside their homes, fewer opportunities for them in education and employment, and greater risk of domestic violence [14]. The other reason might be; women faced different hormonal changes at some stages of their life such as during menstruation cycle, pregnancy, and menopause which may predispose them to emotional changes.…”
Section: Discussionmentioning
confidence: 99%
“…The studies in Tanzania showed that the prevalence of CMD was 24-28.8% [9,12]. In different regions of Ethiopia, the prevalence of CMD ranges from 14.9 to 33.6% [13][14][15].…”
Section: Open Accessmentioning
confidence: 99%
“…Although two articles were identified, they did not describe how epilepsy was diagnosed, and they might not have met our inclusion criteria. 51 52 In the future, larger systematic literature reviews that include a wider range of publication years, more diverse samples, and studies with more consistent diagnostic evaluations could provide a better understanding of the prevalence of psychiatric comorbidity in PWE. Finally, this study performed a qualitative analysis, and thus might not have been able to identify gaps in clinical care.…”
Section: Limitationsmentioning
confidence: 99%
“…Twentythree primary studies were included in the present systematic review and meta-analysis. These studies were conducted in different parts of Ethiopia (from Amhara seven primary articles [7,[13][14][15][16][17][18], Oromiya eight [8,9,[19][20][21][22][23][24], Addis Ababa four [25][26][27][28], Tigray two [9,29], and Southern Nation, Nationalities, and People two articles) [30,31]. The sample size of the included primary studies was considerably variable ranging from 121 to 415 participants.…”
Section: 2mentioning
confidence: 99%
“…Regarding the seizurefree period, two studies assessed seizure freedom over one month [6,21], one study over two months [17], two studies over three months [7,14,25], and the remaining studies assessed seizure freedom over at least six months. Concerning the age groups, one study included only pediatric patients [7], two studies included all age group patients [13,19], and the remaining studies included only adult patients [6,8,9,[14][15][16][17][18][20][21][22][23][24][25][26][27][28][29][30][31]. Regarding the antiepileptic drugs, most of the patients were treated with monotherapy and the commonly used drugs were phenobarbitone, phenytoin, carbamazepine, and valproic acid [6-8, 17, 20, 26].…”
Section: 2mentioning
confidence: 99%